A novel approach to reduce air pollution through machine learning based PM2.5 prediction - Alif, Omar Farhad; Monsaif, Tarik Monwar; Amarth, Swakshar Das; Kabir, Md. Nafiu; Sadman, Tahmid Asif (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.